2014
DOI: 10.1371/journal.pone.0093419
|View full text |Cite
|
Sign up to set email alerts
|

Cultivated Vaginal Microbiomes Alter HIV-1 Infection and Antiretroviral Efficacy in Colonized Epithelial Multilayer Cultures

Abstract: There is a pressing need for modeling of the symbiotic and at times dysbiotic relationship established between bacterial microbiomes and human mucosal surfaces. In particular clinical studies have indicated that the complex vaginal microbiome (VMB) contributes to the protection against sexually-transmitted pathogens including the life-threatening human immunodeficiency virus (HIV-1). The human microbiome project has substantially increased our understanding of the complex bacterial communities in the vagina ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 54 publications
4
69
0
2
Order By: Relevance
“…Recent studies employing cultivation-independent molecular approaches showed that the vaginal microbiome (VMB) is much more complex than previously appreciated and that conventional culture techniques are limited, allowing the detection of only a small fraction of the microorganisms in the vaginal flora (29,30). Therefore, detailed studies on the effects of QAS on the VMB, employing genetically controlled ex vivo models in combination with cultivation-independent methods (31,32), should be performed in the future. This kind of approach will allow a more detailed analysis of the effects of QAS not only on healthy VMB but also on dysbiotic VMB collected from patients with bacterial vaginosis (32), the most common cause of vaginal infection in women of childbearing age, a main factor of increased susceptibility to infection by HIV and other STI (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies employing cultivation-independent molecular approaches showed that the vaginal microbiome (VMB) is much more complex than previously appreciated and that conventional culture techniques are limited, allowing the detection of only a small fraction of the microorganisms in the vaginal flora (29,30). Therefore, detailed studies on the effects of QAS on the VMB, employing genetically controlled ex vivo models in combination with cultivation-independent methods (31,32), should be performed in the future. This kind of approach will allow a more detailed analysis of the effects of QAS not only on healthy VMB but also on dysbiotic VMB collected from patients with bacterial vaginosis (32), the most common cause of vaginal infection in women of childbearing age, a main factor of increased susceptibility to infection by HIV and other STI (29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, detailed studies on the effects of QAS on the VMB, employing genetically controlled ex vivo models in combination with cultivation-independent methods (31,32), should be performed in the future. This kind of approach will allow a more detailed analysis of the effects of QAS not only on healthy VMB but also on dysbiotic VMB collected from patients with bacterial vaginosis (32), the most common cause of vaginal infection in women of childbearing age, a main factor of increased susceptibility to infection by HIV and other STI (29). QAS, being neutral salts, will not alter vaginal pH directly, but indirect effects through alterations of the VMB cannot be excluded at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…DNA or RNA was extracted on an automated MagNA Pure 96 (Roche). VMBs were characterized by customized qPCR array as described previously [17]. Any VMB samples molecularly positive for STI, yeast or Y chromosome were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Immortalized human VEC (V19I and BVEC02I) were cultured as described [20] and used to produce stratified squamous vaginal multilayers [17, 18]. Briefly, VEC from one of 2 donors were plated in 24 (10 6 cells/transwell) or 96 (10 5 cells/transwell) well transwell format and cultured at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation